2020
DOI: 10.1021/acs.est.9b06022
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal-Mediated Cryptic Selenium Cycle Linked to Manganese Biogeochemistry

Abstract: Selenium (Se) redox chemistry is a determining factor for its environmental toxicity and mobility. Currently, millions of people are impacted by Se deficiency or toxicity, and in geologic history, several mass extinctions have been linked to extreme Se deficiency. Importantly, microbial activity and interactions with other biogeochemically active elements can drastically alter Se oxidation state and form, impacting its bioavailability. Here, we use wet geochemistry, spectroscopy, and electron microscopy to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 60 publications
(122 reference statements)
1
36
0
Order By: Relevance
“…Abiotic controls were also prepared using the two filtered wastewater types. AY growth media abiotic controls were not established for this study, as previous work has consistently identified negligible (i.e., ≤1%) Se removal in abiotic systems without fungi ( Rosenfeld et al, 2017 , 2020 ). Ethanol-killed biomass controls were also assembled for the two filtered wastewater types.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Abiotic controls were also prepared using the two filtered wastewater types. AY growth media abiotic controls were not established for this study, as previous work has consistently identified negligible (i.e., ≤1%) Se removal in abiotic systems without fungi ( Rosenfeld et al, 2017 , 2020 ). Ethanol-killed biomass controls were also assembled for the two filtered wastewater types.…”
Section: Methodsmentioning
confidence: 99%
“…Air-dried biomass and filters were digested along with the MCE filter in an individual perfluoroalkoxy (PFA) bottle (Thermo Fisher Scientific) by adding 4.5 mL trace metal grade nitric acid and 0.5 mL hydrogen peroxide, as described previously ( Rosenfeld et al, 2017 , 2020 ). Samples were diluted 1:1 and analyzed by Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) in the Analytical Geochemistry Laboratory at the University of Minnesota.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations